1980
DOI: 10.1111/j.1365-2621.1980.tb03878.x
|View full text |Cite
|
Sign up to set email alerts
|

MODIFIED ATMOSPHERE STORAGE OF ROCKFISH (Sebastes miniatus) AND SILVER SALMON (Oncorhynchus kisutch)

Abstract: Rockfish (Sebastes miniatus) fillets and salmon (Oncorhynchus kisutch) steaks were held in atmospheres containing 20% or 40%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 10 publications
1
35
0
1
Order By: Relevance
“…Values from these parameters were within the acceptable ranges for fresh fish as defined by Connell (1978). This is in agreement with Brown et al (1980) who showed that, for rockfish held in refrigerated storage, ammonia and TMA analyses provide redundant results. Oxidation-reduction potential (Eh) Initial measurements of Eh gave values of about +310 mv.…”
Section: Ammoniasupporting
confidence: 94%
“…Values from these parameters were within the acceptable ranges for fresh fish as defined by Connell (1978). This is in agreement with Brown et al (1980) who showed that, for rockfish held in refrigerated storage, ammonia and TMA analyses provide redundant results. Oxidation-reduction potential (Eh) Initial measurements of Eh gave values of about +310 mv.…”
Section: Ammoniasupporting
confidence: 94%
“…In the present research, non-acceptable scores were obtained at day 17 for the fresh and oxidized odor assessment in raw fish and for the neutral flavor determination in cooked fish. In previous research (Brown et al, 1980), wild Coho salmon showed a slime appearance when refrigerated (4.5ºC) for 7 days, so that it was considered rejectable. In a further study (Barnett et al, 1991), wild Coho salmon was kept in ice up to 14 days; results obtained from the sensory analysis showed that the fish remained at the premium grade for about 7 days, followed by a short period of average sensory quality, becoming borderline after 13 days.…”
Section: Assessment Of Sensory Descriptors In Chilled Coho Salmonmentioning
confidence: 99%
“…However, research concerning the chemical composition characteristics and changes occurring during technological treatment of this species are scarce when compared to other salmonid species (Vinagre et al, 2011). Sensory, chemical, and microbiological changes occurring in wild Coho salmon stored at refrigerated conditions have been analyzed (Brown et al, 1980;Barnett et al, 1991;Luong et al, 1992). For cultivated Coho salmon, high-pressure technology was tested and found to enhance the shelf life during chilled storage (Aubourg et al, 2013), and slurry ice has been proven by Rodríguez et al (2010) to be a pre-treatment for quality preservation for Coho salmon canning.…”
mentioning
confidence: 99%
“…A quality study was conducted to evaluate sensory, chemical, and microbiological changes occurring in wild coho salmon stored in refrigerated conditions (4.5°C) under modified atmospheres (Brown et al, 1980). For this, salmon steaks were held in an atmosphere containing 20% or 40% CO 2 (balance air), with or without 1% CO, being compared to air-control atmosphere.…”
Section: Fresh and Refrigerated Productsmentioning
confidence: 99%